2006
DOI: 10.1021/ed083p501
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning: A Viable Alternative to the Conventional Lecture-Lab Format in General Chemistry

Abstract: Student performance in two first-semester general chemistry courses are compared to determine whether a distance learning model can provide a comparable learning opportunity to the conventional lecture–laboratory format. The conventional course was taught at a midsized, southeastern university; the distance learning course was taught through a community college. The laboratory portion of the distance learning course consisted of at-home (kitchen chemistry) experiments. For the first two semesters (Version I), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
85
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 3 publications
3
85
0
5
Order By: Relevance
“…Nevertheless, a number of studies in various disciplines have reported results suggesting that a virtual or at-home laboratory can be comparable to the traditional laboratory in terms of learning outcomes (Casanova et al 2006;Dobson 2009;Feig 2010). Brinson (2015) completed a comprehensive review of empirical studies comparing the effectiveness of traditional and nontraditional (online) labs, using a model he developed for categorizing learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a number of studies in various disciplines have reported results suggesting that a virtual or at-home laboratory can be comparable to the traditional laboratory in terms of learning outcomes (Casanova et al 2006;Dobson 2009;Feig 2010). Brinson (2015) completed a comprehensive review of empirical studies comparing the effectiveness of traditional and nontraditional (online) labs, using a model he developed for categorizing learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several academic institutions have adopted this approach by successfully developing and offering these laboratory experiences for their distance general chemistry students in B.Sc. programs (Casanova, Civelli, Kimbrough, Heath, & Reeves, 2006;Jeshofnig & Jeshofnig, 2011;Kennepohl, 2007;Lyall & Patti, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they recommended that virtual laboratories be used under conditions of overcrowded classrooms, when tutoring is limited and there is a lack of coordination between the lecture and laboratory materials. Although virtual laboratories can be expensive and time‐consuming to create, they can provide students with experiments that can be repeated as often as necessary, from any location, at no additional cost in resources or personnel (Casanova and others ). Although virtual lab exercises may teach the concepts that a traditional lab also seeks to impart, some educators feel that students who are only exposed to virtual labs do not gain critical hands‐on familiarity with laboratory techniques as compared to students who have traditional science lab experiences (Carnevale ).…”
Section: Introductionmentioning
confidence: 99%